The role of insect pollinators in avocado production: A global review - Dymond, Keira; Celis‐Diez, Juan L.; Potts, Simon G.; Howlett, Brad G.; Willcox, Bryony K.; Garratt, Michael P. D. (Journal of applied entomology (1986), 2021)
Insect pollination increases the yield and quality of many crops and therefore, understanding the role of insect pollinators in crop production is necessary to sustainably increase yields. Avocado Persea americana benefits from insect pollination, however, a better understanding of the role of pollinators and their contribution to the production of this globally important crop is needed. In this study, we carried out a systematic literature review and meta‐analysis of studies investigating the pollination ecology of avocado to answer the following questions: (a) Are there any research gaps in terms of geographic location or scientific focus? (b) What is the effect of insect pollinators on avocado pollination and production? (c) Which pollinators are the most abundant and effective and how does this vary across location? (d) How can insect pollination be improved for higher yields? (e) What are the current evidence gaps and what should be the focus of future research? Research from many regions of the globe has been published, however, results showed that there is limited information from key avocado producing countries such as Mexico and the Dominican Republic. In most studies, insects were shown to contribute greatly to pollination, fruit set and yield. Honeybees Apis mellifera were important pollinators in many regions due to their efficiency and high abundance, however, many wild pollinators also visited avocado flowers and were the most frequent visitors in over 50% of studies. This study also highlighted the effectiveness of stingless bees (Meliponini) and blow flies (Calliphoridae) as avocado pollinators although, for the majority of flower visitors, there is a lack of data on pollinator efficiency. For optimal yields, growers should ensure a sufficient abundance of pollinators in their orchards either through increasing honeybee hive density or, for a more sustainable approach, by managing wild pollinators through practices that protect or promote natural habitat.